Analisis Teori Produksi Dalam Islam: Studi Komparasi Pemikiran Muhammad Abdul Mannan Dan Monzer Kahf - Irsyad, Fairuz Azzahra; Sugianto, Sugianto (ITB AAS INDONESIA Surakarta, 2024)
The aim of this research is to analyze production theory according to Mannan and Kahf. This research is a library study research with a qualitative descriptive method. Data was obtained through literature study and documentation techniques, and analyzed through data reduction, data presentation, and drawing conclusions. The study findings explain that the principle of production according to Mannan is economic prosperity. Management of resources wisely, paying attention to morals, environmental ethics, and in accordance with Islamic law. Factors of production: land, labor, capital, and organization. Meanwhile, according to Kahf, the aim of production is to improve material and moral conditions. Management and use are reasonable, and in accordance with Islamic law. Factors of production: land, labor and capital. This study has implications for scientific knowledge, especially Islamic production theory and can be used as a reference for Muslim business actors in carrying out production processes that prioritize welfare and moral principles in accordance with Islamic law.